Management of international financial institutions - Saxena R. B. (Delhi: Tilak Wasn Discovery Publishing House, 1985)
One of the major functions of the international institutions is to provide financial assistance to its member-countries it may further be noticed that that the less developed countries which are trying to embark on the path of economic development, trying to achieve self- sustained growth, need more financial assistance than do the developed countries of Europe.
Includes bibliographical references and index
uaa 24/01/19
Loans.
Keywords: International Finance; Financial institutions